Quantifying the Temporal Dynamics of Marine Biodiversity Under Anthropogenic Impacts Using eDNA Metabarcoding - Zhewei Si; Wu Han; Tsz Ying Chan; Gert‐Jan Jeunen; Cheng Qian; Isis Guibert; Cheuk Fung Wong; David Baker; Mathew Seymour (Environmental DNA, 2025)
ABSTRACT Marine biodiversity is rapidly declining due to anthropogenic activities; however, the key causal agents of this decline remain largely elusive. Improving our understanding of anthropogenic impact on biodiversity dynamics requires fine‐scale temporal observations, which are logistically challenging using traditional methods. Coral reef ecosystems are key biodiversity hotspots for a wide range of organisms, making them essential for wider marine ecosystem stability and important focal points for marine biodiversity dynamics research. The use of autonomous reef monitoring systems (ARMS) has been effective in assessing reef benthic biodiversity. However, it remains unknown how ARMS marine biodiversity changes over time or in response to anthropogenic activity. Here, we utilized eDNA and a full factorial experiment consisting of 12, 2,042 L mesocosms, seeded with ARMS previously colonized from natural reef habitats. A total of 240 eDNA samples were collected over 20 time points across 232 days to assess: (1) eDNA accumulation dynamics, (2) effects of anthropogenic activity on biodiversity dynamics and (3) eDNA degradation rates. Biological communities changed drastically over time, with 814 ASVs across 617 marine families identified over the course of the experiment. Arthropoda dominated during the accumulation phase, Mollusca during the treatment phase, and Platyhelminthes and Bacillariophyta during the degradation phase. Richness across all mesocosms increased to 110 ± 18 initially, then stabilized at 147 ± 31 during the treatment phase before declining rapidly to 49 ± 17 during the degradation phase. We found that fish feed had a significant negative effect on community composition over time (p < 0.01). Additionally, we identified Lithodesmiaceae and Haminoeidae as potential bioindicator groups. eDNA decay rates across species groups showed faster declines for fish compared to algae and invertebrates. Overall, our findings demonstrate that eDNA metabarcoding offers a detailed assessment of biodiversity, allowing us to differentiate between spatiotemporal and anthropogenic impacts on community dynamics.